Manufacturing Symbolism of Macrolytic Stone Tools in the Yamnaya Culture Funeral Rite of Southern Urals and Middle Volga Region - Nina L. Morgunova; Airat A. Faizullin (Нижневолжский археологический вестник, 2023)
The paper summarizes for the first time a special study data of macrolithic stone tools from the burials of the Yamnaya culture in the Western Orenburg and the Samara Volga regions. The study is based on the results of traceological analysis of 16 stone macrotools. All the tools were mainly products in the form of massive and heavy elongated pestles made of large pebble stone. The following groups of tools were identified: 1) tools for metal production; 2) pestles for rubbing and processing plants; 3) impact tools, chippers for stone processing. The tools associated with metalworking predominate numerically and include pestles for crushing ore, blacksmith hammers, anvils and tools for surface treatment of finished copper products. Often the tools were used for multiple purposes: at first in metal production, and later, perhaps already in the course of the funeral ceremony, for processing plants used in the manufacture of bedding, bedspreads and pillows for decorating graves. As a result, attention was drawn to the placement of metalworking tools in extraordinary kurgans with extraordinary burials including Utevka I, Krasnosamarskoe I, Boldyrevo I, and Tamar-Utkul VII. All the burials in which this group of artifacts was found are characterized by high labor costs significantly exceeding the standards of most known Yamnaya culture kurgan. The finds made of stone in the burials were found in combination with metal tools, weapons, sacral symbols and metal ornaments. The conclusion is made that there is a symbolic indication made by the stone tools of a specific occupattion of the buried individuals and their belonging to certain clans associated with the most important industries for pit collectives, primarily with metal production, mining of copper ore and its processing. According to the authors, a complex combination of both industrial and military, and cult-religious symbols in the largest and most significant burial structures of the Yamnaya culture in the Volga-Urals is typical of the burials of super leaders at the pre-political stage of society development.